HIV testing, antiretroviral therapy, and treatment outcomes in new cases of tuberculosis in Brazil, 2011 - Ana Torrens; Patricia Bartholomay; Silvano Silva; Mohammed Khogali; Kristien Verdonck; Karen Bissell
ABSTRACT Objective To assess the implementation of HIV-related interventions for patients with tuberculosis (TB), as well as TB treatment outcomes in patients coinfected with HIV in Brazil in 2011. Methods This was a cross-sectional, operational research study of HIV-related interventions among TB cases and the sociodemographic and clinical characteristics of TB-HIV coinfected patients. It also used a retrospective cohort design to determine the association between antiretroviral therapy (ART) and favorable TB treatment outcomes. The source of data was a linkage of 2011 administrative health databases used by the National TB and HIV/AIDS Programs. Results Of 73 741 new cases of TB reported, 63.6% (46 865 patients) were tested for HIV; 10.3% were positive. Of patients with HIV, 45.9% or 3 502 were on ART. TB favorable outcome was achieved in 63.1% or 2 205 coinfected patients on ART and in only 35.4% or 1 459 of those not on ART. On multivariate analysis, the relative risk for the association between ART and TB treatment success was 1.72 (95% Confidence Interval = 1.64-1.81). Conclusions The linkage between national TB and HIV datasets has created a convenient baseline for ongoing monitoring of HIV testing, ART use, and TB treatment outcomes among coinfected patients. The low rates of HIV screening and ART use in 2011 need to be improved. The association between ART and treatment success adds to the evidence supporting timely initiation of ART for all patients with TB-HIV coinfection.